Spatial downscaled future food demand V1 - Song, Chun; Yego, Francis Kipkogei (Harvard University, 2025)
This dataset contains V1 spatially downscaled future food demand from IMPACT for major food groups in 2005 and 2030 under the reference scenario. For more detail, please see "Method."